Learning numerals for down syndrome by applying cognitive principles in 3D walkthrough / Nor Intan Shafini Nasaruddin ... [et al.] - Nasaruddin, Nor Intan Shafini; Ismail, Khairul Nurmazianna; A.Halim, Aleena Puspita (2015)
Down Syndrome (DS) is a condition where extra genetic chromosomes cause delay in children development either mentally or physically. However the cognitive ability can be develop with the help of surrounding people and technology. Many available applications provided for children with learning difficulties like DS. However there are only a few of them that help in numerical learning. Due to the problem stated, this research study to provide an application that help the DS children range of four to five years olds in learning numerals (one to ten) in an interactive way applying the cognitive principles attention and memory using the walkthrough work frame. The effectiveness and the usability of this application are evaluated through testing and questionnaires. The projects were successful met the objective of the research.